Destination image, satisfaction and destination and loyalty in cruise tourism: the case of Málaga (Spain) - Cruz-Ruiz, Elena de los Reyes; Bermúdez-González, Guillermo José; Tous-Zamora, Dolores (My University, 2016)
Over the past decades cruise tourism is a sector that has experienced a tremendous growth around the globe. The relations that are established between the different agents that interact in this industry, passengers, crew and residents are crucial for visitor satisfaction and the success of the tourist destination. The study has analyzed the different types of cruise passengers who landed at the port of Malaga and their perception of the city through destination image, satisfaction and destination loyalty. A cluster analysis identified the existence of four different groups of passengers whose opinions can give a specific answer to the consolidation of Malaga as a quality tourist destination. From a practical point of view, recommendations about the adequate management of the destination´s attractions for the cruise industry are discussed in the conclusions.
Keywords: Turismo; Cluster analyisis; Destination image; Destination loyalty; Cruise tourism